Acrolein Exposure in U.S. Tobacco Smokers and Non-Tobacco Users: NHANES 2005–2006 - Alwis, K. Udeni (Environ Health Perspect, 2015)
BACKGROUND: Acrolein is a highly reactive α,β unsaturated aldehyde and respiratory irritant. Acrolein is formed during combustion (e.g., burning tobacco or biomass), during high-temperature cooking of foods, and in vivo as a product of oxidative stress and polyamine metabolism. No biomonitoring reference data have been reported to characterize acrolein exposure for the U.S. population. OBJECTIVES: Our goals were to a) evaluate two acrolein metabolites in urine—N-acetyl-S-(3-hydroxypropyl)-l-cysteine (3HPMA) and N-acetyl-S-(2-carboxyethyl)-l-cysteine (CEMA)—as biomarkers of exposure to acrolein for the U.S. population by age, sex, race, and smoking status; and b) assess tobacco smoke as a predictor of acrolein exposure. METHODS: We analyzed urine from National Health and Nutrition Examination Survey (NHANES 2005–2006) participants ≥ 12 years old (n = 2,866) for 3HPMA and CEMA using ultra-high-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (UPLC/ESI-MSMS). Sample-weighted linear regression models stratified for non-tobacco users versus tobacco smokers (as defined by serum cotinine and self-report) characterized the association of urinary 3HPMA and CEMA with tobacco smoke exposure, adjusting for urinary creatinine, sex, age, and race/ethnicity. RESULTS: 3HPMA and CEMA levels were higher among tobacco smokers (cigarettes, cigars, and pipe users) than among non-tobacco users. The median 3HPMA levels for tobacco smokers and non-tobacco users were 1,089 and 219 μg/g creatinine, respectively. Similarly, median CEMA levels were 203 μg/g creatinine for tobacco smokers and 78.8 μg/g creatinine for non-tobacco users. Regression analysis showed that serum cotinine was a significant positive predictor (p < 0.0001) of both 3HPMA and CEMA among tobacco smokers. CONCLUSIONS: Tobacco smoke was a significant predictor of acrolein exposure in the U.S. population. CITATION: Alwis KU, deCastro BR, Morrow JC, Blount BC. 2015. Acrolein exposure in U.S. tobacco smokers and non-tobacco users: NHANES 2005–2006. Environ Health Perspect 123:1302–1308; http://dx.doi.org/10.1289/ehp.1409251